PERADABAN PEMERINTAHAN ARAB: ANALISIS KRITIS BUKU HADHARATUL ‘ARAB KARYA GUSTAVE LE BON - Hafidhah Syafni; Rahmania Auriel Zaeni; Miftahul Huda; Nur Kholid (Kalam: Jurnal Agama dan Sosial Humaniora, 2024)
“Hadharatul ‘Arab” is a book that created by Gustave Le Bon in 1884. This article currently presents critical analysis about this book, especially how the writer wrote and explained it to the reader. The purpose of this article is to present an analysis of the way an orientalist wrote about Islamic history and compare the methods of presenting the material in this book with other references in order to know the various ways of writing history. In writing this article, the researchers used a descriptive qualitative method which centred on library research or literature review. The theory used in analysing the book “Hadharatul ‘Arab” is discourse analysis. And the central chapter of study in this discussion is about “the civilisation of the Arab government”. In this discussion is explained about the biography of Gustave Le Bon, the identity of the book "Hadharatul 'Arab", how Gustave presented the material of the book which focus on the Arab government, the positive and negative sides of the presentation, as well as comparing the methods used in it with other books. After analysing, the researchers mentioned that there is no definite standard in history presentation, all presentations have a different focus in conveying their purpose, and all of them can be a reference in the scientific field of historical science.